EXPRESS: Surgical management of bilateral atypical tibial fractures associated with long-term bisphosphonate therapy in a cat - Justin Koh Wei Wong; Stephanie Colthurst (Journal of Feline Medicine and Surgery Open Reports, 2026)
An eight-year-old, indoor, male neutered Oriental mix cat was presented with acute bilateral pelvic limb lameness without preceding trauma. The cat had received oral alendronate for 4.5 years for the management of idiopathic hypercalcaemia. Radiographs revealed bilateral, closed, comminuted proximal tibial and fibular fractures with cortical sclerosis. Staged bilateral open reduction and internal fixation were performed using orthogonal locking compression plates. Alendronate therapy was discontinued, and the cat remained normocalcaemic during eight months of follow-up. Despite robust stabilisation, traumatic re-fracture of the right tibia occurred following inadequate confinement, necessitating revision fixation with longer implants and the addition of allogeneic demineralised bone matrix (DBM). Delayed union and marked callus formation were observed in the left tibia, consistent with suppressed bone remodelling secondary to chronic alendronate therapy. In contrast, the revised right tibial fracture, treated with adjunctive DBM, demonstrated accelerated healing. Radiographic monitoring demonstrated osseous union without further complications or evidence of additional fractures, illustrating that favourable outcomes are achievable in cats with bilateral bisphosphonate-associated insufficiency fractures when appropriately managed. This report represents the second documented case of bisphosphonate-associated fractures in a cat managed surgically with extensive follow-up. It is the first to describe bilateral tibial fracture repair and the use of adjunctive DBM for bisphosphonate-associated fractures. It highlights that favourable outcomes are achievable in these cases through orthogonal plating combined with adjunctive DBM, and discontinued bisphosphonate therapy to reduce future fracture risk. This report also supports serial radiographic monitoring, particularly within five years of treatment initiation.